(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The Italian Constitutional Court, with its judgment no. 162/2014, repealed the ban on assisted reproductive technology (ART) with gametes’ donation. This paper deals with the right of the offspring to know his/her origins. This right should be (at least, partially) recognised because of the protection of psychological health and identity granted by the Italian Constitution. Both have to be understood in the light of the case law of the European Court of Human Rights. The current debate concerning ART with gametes’ donation, however, is not taking these aspects into account. The paper exposes the legislation in Germany, Austria, Switzerland and UK. The first country didn’t regulate the matter and is now confronted with remarkable problems. The last amended its legislation some years ago and could provide useful elements for a future Italian regulation.